Analysis and Application Design Career Development Center in The STMIK Insan Pembangunan (Case Study: Information Study Program) - Safrizal, Safrizal; Budiadyana, Gusti Nyoman (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2019)
In order to facility data of ex-graduate maintaining and career information distribution to all of member of STMIK Insan Pembangunan especially Information System, information system is made to handle that. It is an application that named Career Development Center. In processing that aplication, the writer do examination by interview, observation and from books or literatures and then continue to model it with UML diagrams. Along with this system, it is hoped that recapitulaton of ex-graduate and career information spreading about job vacancy, tips and training/workshop can help user to maintain it.